The structure of genetic and environmental risk factors for fears and phobias. Issue 11 (August 2014) - Loken, E. K.; Hettema, J. M.; Aggen, S. H.; Kendler, K. S.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although prior genetic studies of interview-assessed fears and phobias have shown that genetic factors predispose individuals to fears and phobias, they have been restricted to the DSM-III to DSM-IV aggregated subtypes of phobias rather than to individual fearful and phobic stimuli. Method We examined the lifetime history of fears and/or phobias in response to 21 individual phobic stimuli in 4067 personally interviewed twins from same-sex pairs from the Virginia Adult Twin Study of Psychiatric and Substance Abuse Disorders (VATSPSUD). We performed multivariate statistical analyses using Mx and Mplus. Results The best-fitting model for the 21 phobic stimuli included four genetic factors (agora-social-acrophobia, animal phobia, blood-injection-illness phobia and claustrophobia) and three environmental factors (agora-social-hospital phobia, animal phobia, and situational phobia). Conclusions This study provides the first view of the architecture of genetic and environmental risk factors for phobic disorders and their subtypes. The genetic factors of the phobias support the DSM-IV and DSM-5 constructs of animal and blood-injection-injury phobias but do not support the separation of agoraphobia from social phobia. The results also do not show a coherent genetic factor for the DSM-IV and DSM-5 situational phobia. Finally, the patterns of co-morbidity across individual fears and phobias produced by genetic and environmental influences differ appreciably.